2013
DOI: 10.4236/ajibm.2013.34043
|View full text |Cite
|
Sign up to set email alerts
|

Integration of ISO 31000:2009 and Supply Chain Risk Management

Abstract: Supply chain risk management (SCRM) can provide companies with a long-term competitive advantage, particularly if it is integrated with enterprise risk management (ERM). Current SCRM research frameworks do not explicitly examine this integration, potentially hindering a deeper understanding of SCRM. This research uses survey data and follow-up interviews to suggest that ISO 31000:2009 provides a foundation for advancing future SCRM research, and to more successfully execute SCRM. It is also determined that ISO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 40 publications
2
15
0
2
Order By: Relevance
“…Hendricks et al (2009) cite a survey among 151 executives, of whom 73% stated their firms had experienced supply chain disruptions in the past five years and 48% expected the risk to increase in the next three years. Scannell et al (2013) conclude that a risk-oriented supply chain enables firms to obtain strong competitive advantage and provides reliable long-term benefits for all stakeholders.…”
Section: Supply Chain Risk Management (Scrm)mentioning
confidence: 90%
See 1 more Smart Citation
“…Hendricks et al (2009) cite a survey among 151 executives, of whom 73% stated their firms had experienced supply chain disruptions in the past five years and 48% expected the risk to increase in the next three years. Scannell et al (2013) conclude that a risk-oriented supply chain enables firms to obtain strong competitive advantage and provides reliable long-term benefits for all stakeholders.…”
Section: Supply Chain Risk Management (Scrm)mentioning
confidence: 90%
“…Any risk of interruption of the flow between a company and supplier that prevents the supplier from satisfying its commitment to reliability. Diabat et al (2012), Pfohl et al (2010), Scannell et al (2013).…”
Section: Risks Description Authors Supplymentioning
confidence: 99%
“…Regarding the relevance of the theme, Xia & Chen (2011) believe that SCRM has a strong influence on the establishment of cooperation among commercial partners and the performance of the entire chain. In turn, Scannell et al (2013) conclude that a focus on managing risks in supply chains establishes a competitive position and long-term benefits to stakeholders.…”
Section: Risks and Their Management In Supply Chainsmentioning
confidence: 96%
“…Luko [16] reviewed the terminology and language and used the new guidelines as adopted in the United States as ANSI/ASSE Z690.2-2011 and concluded that ISO 31000 provided a good framework for managing quality and business risks through integration. Scannell et al [23] investigated the supply chain risk management (SCRM) approaches and determined that ISO 31000 included the core steps used in SCRM but included two additional steps and so this was more comprehensive. This research also revealed that companies recognised the importance of SCRM but lacked skills and the ability to integrate these into ISO 31000.…”
Section: Published Research On Iso 31000mentioning
confidence: 99%
“…to complement other conventional risk management systems [7,23,24]. This includes systems-based approaches.…”
Section: Iso 31000 Supplemented Other Risk Management Strategiesmentioning
confidence: 99%